Oxford popular school dictionary - Hawkins, Joyce; Delahunty, Andrew McDonald, Fred (Oxford University Press Oxford, 2002)
Offering students a head start at school and at home, this book serves as a reference tool for students with dictionary skills who are not yet ready to use an adult dictionary. It contains definitions, phrases, and sample sentences.